Comparação de dois modos de ventilação não invasiva (ventilação assistida proporcional e ventilação com pressão de suporte) no pós-operatório de revascularização do miocárdio - Silva, Fábia Diniz (2009)
Pulmonary complications in the postoperative (PO) in cardiac surgery (CS) are frequent, besides being seen as the main motive for prolonging hospitalization, morbidity, and mortality. Noninvasive ventilation (NIV) is used in the postoperative to avoid or reverse pulmonary damage. This study compares two modes of NIV, using either pressure support ventilation (PSV) or proportional assist ventilation (PAV) in the postoperative of coronary artery bypass grafting surgery. It also assesses safety, dyspnea sensation, and gas exchanges, besides verifying which mode is more comfortable to the patient. Twenty-five patients were randomized into two groups: thirteen ones made NIV in PAV; twelve ones in PSV. Arterial gasometry was made with patient breathing ambient air; and chest radiographs were made before the study began and after the last NIV session. Two daily sessions of NIV were carried out, each of them during 30 minutes for two days. Heart rate and arterial pressure were verified before NIV begins, ten minutes and twenty minutes after its beginning, then after each one of its sessions. Peripheral oxygen saturation (SpO2) and respiratory rate (RR) were measured before NIV sessions beginning, at 5, 10, 15, 20, 25 minutes after it, then after each one of its sessions. Tidal volume, minute ventilation, maximum inspiratory pressure, fraction of inspired oxygen (FiO2), PS, volume assist, flow assist, and proportionality were recorded at 5, 15, and 25 minutes. Positive end expiratory pressure (PEEP) was established in 5 cmH2O. Scale for level of comfort and modified Borg scale for dyspnea were applied. The PAV group showed a higher SpO2 than the PSV group. Although RR decreased (p < 0,001) in the two groups during NIV, it was higher in the PAV, which showed a MIP (p < 0,01) lower than the PSV group. There was a reduction in arterial pressure of carbon dioxide (PaCO2) and in dyspnea perception in the two groups. No difference was found out in the comfort scale. Results show that PAV and PSV modes are safe and reduce dyspnea sensation; that PAV presented a lower MIP; that PAV and PSV modes were comfortable and reduced patient s dyspnea sensation; and that PAV mode presented a relevant reduction in MIP when compared to PSV mode.